2008
DOI: 10.1080/13550280802304746
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive changes in asymptomatic drug-naïve human immunodeficiency virus type 1 clade C infection

Abstract: Asymptomatic human immunodeficiency virus (HIV) infection is associated with impaired cognitive functioning in both clade B and C infections. The nature of cognitive change longitudinally has not been studied in asymptomatic clade C infection. The present study evaluated changes in neuropsychological functioning over a 2(1/2)-year period in a cohort of HIV-1 clade C-infected asymptomatic individuals from South India. Participants with CD4 counts below 250 were started on highly active antiretroviral therapy (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Finally, the study is cross-sectional in nature and it will be important to understand the long-term outcome of individuals infected with clade C who do and do not exhibit the C31 substitution. Interestingly, Gopukumar et al (2008) reported no significant decline in cognitive function over a two-year and one half-year period among individuals infected with clade C HIV residing in India. Since the Tat C31 substitution is more conserved in this population than in South Africa (Rao et al 2013) it is unclear how cognitive impairment progresses among individuals with and without the Tat substitution in South Africa and therefore additional studies are needed to address this concern.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, the study is cross-sectional in nature and it will be important to understand the long-term outcome of individuals infected with clade C who do and do not exhibit the C31 substitution. Interestingly, Gopukumar et al (2008) reported no significant decline in cognitive function over a two-year and one half-year period among individuals infected with clade C HIV residing in India. Since the Tat C31 substitution is more conserved in this population than in South Africa (Rao et al 2013) it is unclear how cognitive impairment progresses among individuals with and without the Tat substitution in South Africa and therefore additional studies are needed to address this concern.…”
Section: Discussionmentioning
confidence: 96%